2023
DOI: 10.1002/ejic.202300283
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Singlet Oxygen Sensitization by Antimony (III/V) Corrole Complexes

Abstract: The synthesis, structural, spectroscopic characterization, and DFT/TD‐DFT calculations of antimony corroles are reported herein. The studied complexes can be described as [(Corr)SbIII] and [(Corr)(oxo)SbV]2, where Corr is the trianion of corrole. All these complexes are diamagnetic in nature as is evident from sharp peaks with normal chemical shifts in the 1H NMR spectra. Single crystal XRD analysis reveals that the antimony(V) corrole complex is the bis‐μ‐oxo‐bridged dinuclear antimony(V). Both the tetra and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The synthesis of antimony corrole may be traced back two decades ago. 21 Contemporary research on antimony corrole encompasses photocatalytic oxidation, [22][23][24][25][26] photodynamic inactivation of mold spores, 27 and electrocatalytic oxygen evolution reactions. 28 However, the application of antimony corrole in the electrocatalytic HER has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of antimony corrole may be traced back two decades ago. 21 Contemporary research on antimony corrole encompasses photocatalytic oxidation, [22][23][24][25][26] photodynamic inactivation of mold spores, 27 and electrocatalytic oxygen evolution reactions. 28 However, the application of antimony corrole in the electrocatalytic HER has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…10 Additionally, Sb( v ) corroles have been researched with respect to their spectroscopic properties and their role in sensitising ground state triplet oxygen ( 3 O 2 ) to 1 O 2 . Previous studies demonstrated the impressive ability of Sb( v ) corroles to facilitate the generation of sulfoxides through singlet oxygen pathways 11,12 or to serve in the photoinactivation of mold spores and green algae. 11…”
mentioning
confidence: 99%